(3GdJVNe eG Hjf GdfXQjI hGdhGbY s ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3GdJVNe h GSJbQGQ GdCSYGQ(B,(3JhbY hGSJgOGa GdJhbY(B,(3WHY GdfbhO haLhI GdfbO hGdJVNe eY bjGS GdJVNe GdcjfRj hGdJVNe GdeSJhQO (B,(3hgfGc CjVG JYbje(B,(3GdeVGYa(B, (3YLR GdehGRfI (B,(3hJaVjd GdSjhdI hGdEbJUGO GdehGRj aj GdJVNje s
(3eQGLY U(B.221s
Keywords: (3GdCSYGQs; (3GdJVNe GdeGdjs; (3GdSjGSI GdeGdjIs